A NOTE ON INTUITIONISTIC ANTI FUZZY BI-IDEALS OF SEMIGROUPS - Thandu Nagaiah; Samit Kumar Majumder; Pasham Narasimha Swamy; Thota Srinivas (Journal of New Theory)
In this paper the notions of intuitionistic anti fuzzy bi-ideal, intuitionistic anti fuzzy interior ideal, intuitionistic anti fuzzy (1,2)-ideal in semigroups are introduced and some important characterizations have been obtained.